O conceito de multiculturalidade em coleções didáticas: uma análise do Manual do Professor do Projeto Araribá de História - MELO, Robson Ferreira (2024)
The present research aims to analyze Multiculturalism in the Araribá project history textbook, “Teacher's Manual” for the 7th year, final years of elementary school, about the temporality of 2008 to 2017. We used as sources the Notices and Guides of the PNLD (National Book and Teaching Material Plan) referring to the period of 2008 and 2017 in addition to 04 printed manuals, these being: Project Araribá 7th year PNLD 2008, Project Araribá 7th year PNLD 2011, Project Araribá 7th year PNLD 2014 and Project Araribá 7th year PNLD 2017 in order to investigate the conceptual approach of Multiculturality in this work. We will use the approach of Lívio Sansone (2007), Marcos Garcia Neira (2022), Mariana Martins da Costa Quinteiro and Lana Cláudia Fonseca (2018), among others, so that they prioritize the development of discussions about multiculturalism. Finally, it is hoped that through this and other research, multiculturalism can be discussed inside and outside the classroom. Where Laws, Teachers and History Teaching Materials come to provide teaching aimed at consolidating multicultural awareness.